The scientific community in COVID-19 global pandemic: A systematic update on recent progress and challenges - Firdaus, Zeba; Singh, Sushil Kumar; Singh, Tryambak Deo; Singh, Meenakshi (European Journal of Chemistry, 2021)
The novel coronavirus, which emerged in China in late December 2019, is officially named as Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). The rapid spread of the virus across the continent has disrupted human life in every aspect leading to health and economic crises. The World Health Organization (WHO) declared the novel coronavirus outbreak as a global pandemic on March 11, 2020. In spite of complete lockdown and quarantine efforts in many countries, the occurrence of infections continues to rise, with more than 88 million laboratory-confirmed cases and over 1.9 million deaths worldwide as on January 10, 2021. Since the beginning of the outbreak, lot of intriguing studies about the phylogenetic evolution, epidemiology, pathogenesis, transmission, clinical characteristics, and possible treatment of Corona Virus Disease 2019 (COVID-19) have been published. This review aims to provide an insight into the progress in this regard and provides a reference for future studies including general awareness. We have discussed the origin, transmission, and infection mechanism of coronaviruses in host cells as well as available treatment options with relevant case studies. Furthermore, the stages of vaccine development, types of vaccines, and candidate vaccines with their phases of clinical trial are also incorporated. In a nutshell, the article is an attempt to retrieve the latest information available on virus behavior, efficacy of the available drugs, and development of candidate vaccines on SARS-CoV-2.